2018
DOI: 10.1507/endocrj.ej17-0471
|View full text |Cite
|
Sign up to set email alerts
|

Identification of urinary biomarkers for the prediction of gestational diabetes mellitus in early second trimester of young gravidae based on iTRAQ quantitative proteomics

Abstract: Gestational Diabetes Mellitus (GDM) has brought great harm to maternal and fetus. Up to now, only a few plasma biomarkers for its early diagnosis have been reported; nevertheless, there is no report about identification of urinary biomarkers for prediction of GDM. Thus, it is necessary to correct this deficiency. In our study, urine samples were collected from 889 healthy young gravidae at the early second trimester (15 to 20 weeks), 69 of whom were subsequently diagnosed with GDM at 24 to 28 weeks. iTRAQ (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…A specific protein or metabolite pattern will help to decipher biological processes in a more holistic way. These metabolic “fingerprints” of different body fluid sources could then be used for predictive purposes as has already been demonstrated in small case-control studies ( 48 , 63 ).…”
Section: Methods For Early Gdm Screeningmentioning
confidence: 90%
“…A specific protein or metabolite pattern will help to decipher biological processes in a more holistic way. These metabolic “fingerprints” of different body fluid sources could then be used for predictive purposes as has already been demonstrated in small case-control studies ( 48 , 63 ).…”
Section: Methods For Early Gdm Screeningmentioning
confidence: 90%
“…Urine samples from patients with GDM have been studied in several ways, for example, the group of Guo et al using iTRAQ (the isobaric tags for relative and absolute quantification) for quantitative proteomics found 83 differential proteins increased and 36 proteins decreased in GDM. They concluded that the two candidate protein biomarkers (CD59 and IL1RA) in urine could be early, noninvasive diagnostic predictors of GDM 17 . More recently, López-Hernández et al analyzed the urinary metabolome profile of GDM patients in the 3rd trimester of pregnancy based on liquid chromatography mass spectrometry, and identified 14 metabolites that were significantly up-regulated in the urine of GDM patients 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is also a growing trend for seeking noninvasive testing strategies nowadays. Hence, one study used urine samples to identify biomarkers that could predict GDM [38].…”
Section: Summary Of Proteomic Studies Of Gdmmentioning
confidence: 99%
“…In addition to clinical validation or functional verification, eight studies also performed expression verification experiments using immunodepletion, western blot, immunohistochemistry, real-time polymerase chain reaction, or bioinformatics database (the Human Protein Atlas) [55] to verify the existence, localization, and change trend of DE proteins. Table 1, five studies evaluated the diagnostic efficiency of a selected list of significantly changed proteins [31,37,38,42,47]. The concentrations of target proteins were measured by the ELISA or MRM method in serum, plasma, or urine samples.…”
Section: General Experimental Workflowmentioning
confidence: 99%